Socio-demographic correlates of leisure time physical activity among Portuguese adults - Adilson Marques; João Martins; Hugo Sarmento; Madalena Ramos; José Diniz; Francisco Carreiro da Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
This study aimed to identify socio-demographic correlates of leisure time physical activity among Portuguese adults. Subjects aged 31-60 years (1,076 males, 1,383 females) were categorized into two groups according to recommended physical activities ranging from ≥ 10 or < 10 MET.hours.week-1. Leisure time physical activity data was self-reported, including activities, duration of each session and frequency. Chi-square and logistic regression analyses were applied to the results. Among men, having a high socioeconomic status (OR = 1.89; 95%CI: 1.30-2.76; p = 0.001) was associated with attaining the recommended level of physical activity. For women, middle education levels were associated with physical activity (OR = 1.36; 95%CI: 1.01-1.85). Moreover, middle socioeconomic status (OR = 1.45; 95%CI: 0.80-1.91; p = 0.009) was also positively associated with meeting physical activities recommendations in the unadjusted analysis. Men and women had different patterns of socio-demographic correlates. An intervention designed to improve the levels of physical activity among Portuguese adults may take these correlates into account.